Industrial Relations, Strategic Importance and Decision-Making - Peccei, Riccardo; Warner, Malcom (Relations industrielles / Industrial Relations, 1981)
This study looks at Industrial Relations decision-making in 18 decision-areas, in a multinational firm. It analyses the problem in terms of a model of strategic importance and examines in detail the inter-organizational variance of centralization of the Company's four main product divisions. Substructural autonomy appears to increase with the size of subsidiary, but seems to level off once they have attained a certain size. The average size of subsidiary and average degree of conflict for each of the divisions were also found to be related in a somewhat unexpected way.